Teaching students at a management university to swim with the aim of reducing motor dysfunctions caused by a fear of water - Gerasimov M.V. ,; Mironov A.O. ,; Ponimasov O.E. ,; Fetisov V.N. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to experimentally substantiate methodological techniques that help overcome fear of water among students at a management university. Methods and structure of the study. The sample for the scientific study included 65 university students majoring in management, aged 19.5±0.7 years, who did not know how to swim. To measure the level of fear of water, a fear factor questionnaire was used, adapted to the process of learning to swim and consisting of 10 questions. Basic swimming skills were taught over a period of six weeks, with three 60-minute lessons per week. Results and conclusions. Teaching basic swimming skills leads to a reduction in fear of water. The development of mental qualities in learners, such as endurance and self-control when in the water, is possible through the use of teaching methods for basic swimming skills, which expand the practical scope of their application in an aquatic environment.